The implementation of image-based hidden object games to enhance vocabulary on the theme of "die Schule" in writing skills among Class X-B students at MAN 2 Bojonegoro - Akbari, Yovi; Julaikah, Dwi Imroatu (LATERNE, 2025)
The implementation of image-based hidden object games to enhance vocabulary mastery on the theme of die Schule in writing skills among Class X-B students at MAN 2 Bojonegoro was conducted based on interviews with the subject teacher regarding the issues faced at the school. Students experienced difficulties in memorizing vocabulary, spelling, and writing due to the lack of instructional media available at the school. Therefore, the research problems that could be formulated are how is the implementation of using hidden object game image media and how are the students learning outcomes. This research aims to find out the implementation of using hidden object game image media and to determine the students learning outcomes. This research employed a descriptive qualitative approach. According to Ridwan (2014), the scoring of observations and the results of the pre-test and post-test are calculated using the Likert scale. Furthermore, the implementation results during the teaching and learning process were observed, yielding a score of 26 with a percentage of 73.33% in the first session and a score of 31 with a percentage of 82.22% in the second session. These findings indicated that the learning process during these two sessions was conducted effectively. The learning outcomes, as evidenced by pre-test and post-test scores, showed that 26 out of 34 students (76.43%) demonstrated an improvement, while 8 out of 34 students (23.52%) showed a decline. Based on the results of the research, it can be concluded that the implementation of using hidden object game image media was carried out well, and the learning outcomes of Class X-B students regarding German vocabulary on the theme ’die Schule’ were considered successful. Keyword: Implementation, Media in Hidden Object Game, Vocabulary,Writting Skill.